The early Cambrian tommotiid genus Dailyatia from South Australia - Skovsted, Christian B.; Betts, Marissa J.; Topper, Timothy P.; Brock, Glenn A. (2015)
2-4 in South Australia (Arrowie and Stansbury basins). Six species of Dailyatia are documented and new terminology for describing camenellan sclerites is introduced. Dailyatia sclerites are found in three fundamental sclerite types (A-C), each of which may be present in one to three sub-types depending on species. The previously described species Dailyatia ajax Bischoff1976 and D. macroptera (Tate 1892) are revised and four additional species are described for the first time from South Australia. These include D. odyssei Evans & Rowell 1990, previously known only from Antarctica, and two new species; D. bacata sp. nov. and D. helica sp. nov. as well as a species left under open nomenclature. Two of the recognised species (D. macroptera and D. helica) occur in two different ecophenotypic variants. Species and variants are defined by differences in sclerite types present in the scleritome, sclerite morphology and ornament. The sclerites of Dailyatia are finely laminated with distal expansion of laminae supporting the prominent concentric ribs. The external surface is covered by a fine reticulate network which indicates that the sclerites were at least partly embedded in soft integument. The pattern of incremental growth reveals specific initial and possible gerontic growth stages with unique surface sculptures. Evidence of physical damage and growth disturbances is common in Dailyatia sclerites and many specimens reveal preferential abrasion of the apex. Apical canals are present in all sclerites and are connected to specialised internal apical structures. The internal surface of the sclerites in most species reveals raised platforms and depressed, scar like areas forming unique patterns in each sclerite type, presumably representing muscular attachment. Two specimens revealing ontogenetic fusion of Dailyatia sclerites have been recovered. Based on all available evidence, a new reconstruction of the Dailyatia scleritome is proposed. In the reconstruction, a central row of A and paired B sclerites is flanked on ...